วัสดุซิลิกา-เจลาตินนาโนคอมโพสิตเพื่อเป็นพาหะ สำหรับตัวเร่งปฏิกิริยาชีวภาพ - วาทินี จุลภารพิมล (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The overall aim of this project was to synthesise new material called "silica-gelatin nanocomposite" to be used as a carrier for immobilized enzyme in bioprocesses. The study consists of two main experimental parts. The first part was to investigate suitable conditions for the synthesis of silica-gelatin nanocomposite material. The study covered investigations of effects of influential parameters, namely; pH of solutions, water to tetraethoxysilane (TEOS) concentration (r value), and gelatin concentration on the synthesised material. The material dissolution stabilities in water, various kinds of organic solvents and heat was tested. It was found that the use of 0.1 M HCI as a catalyst in solgel process increased the rate of hydrolysis and condensation reactions and the product obtained was bulk silica gel. r = 4 was chosen because at this value TEOS was not that much diluted and there was still enough water for gelation and enzyme solubilisation. The use of 8%w/v gelatin concentration prevented phase separation during the gelation. The synthesised material obtained under 0.1 M HCI, r=4, and 8%w/v gelatin concentration was transparent and tough due to dominant nanogel network. From the SEM analysis, the material was to be quite homogeneous with smooth surface and the area was 0.29 m2/g(BET equation). Results from 29Si-NMR analysis revealed that the silica network produced contained dominant silicon atoms which beared 3 siloxane bonds and 1 silanol group designated as Q3 species. The material synthesised was found to swell two folds when immersed in either water or various organic solvents (acetone, hexane, cyclohexane, heptane, and isooctane) for a week. Air drying of the solvents swollen samples led to original dense bodies The second part investigated the initial rate of reaction enhancedly immobilized enzyme. The material synthesised was used as a carrier for lipase from Candida cylindracea to catalyse the tranesterification reaction of racemic menthol with hexyl acetate. The initial rate for resolution of racemic menthol by immobilized lipase was found to be 1.5 times higher than that of free enzyme. (100 µmol / l - hr-g enz.) The immobilized lypase exhibited good storage stability with surprisingly 134% and 70% increase in transesterification activity after 15 and 35 days of storage respectively. In contrast, free enzyme was found to lose its activity up to approximately 50% of it origlnal activity.